2019
DOI: 10.1242/jcs.230706
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of chemotropism and cell fusion in unicellular fungi

Abstract: In all eukaryotic phyla, cell fusion is important for many aspects of life, from sexual reproduction to tissue formation. Fungal cells fuse during mating to form the zygote, and during vegetative growth to connect mycelia. Prior to fusion, cells first detect gradients of pheromonal chemoattractants that are released by their partner and polarize growth in their direction. Upon pairing, cells digest their cell wall at the site of contact and merge their plasma membrane. In this Review, I discuss recent work on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 109 publications
(122 reference statements)
2
34
0
Order By: Relevance
“…The exploratory polarization strategy supported by our findings, like the related speed dating strategy proposed for S. pombe (Bendezu and Martin, 2013;Martin, 2019;Merlini et al, 2016), provides an elegant solution to the problem of choosing a partner from among two or more similarly-distant candidates. Classical spatial sensing paradigms that integrate spatial information to extract a single "upgradient" direction are poorly suited to this task, as the presence of two or more nearby chemoattractant sources may create a weak or even non-existent net gradient.…”
Section: Advantages Of Exploratory Polarizationsupporting
confidence: 53%
See 2 more Smart Citations
“…The exploratory polarization strategy supported by our findings, like the related speed dating strategy proposed for S. pombe (Bendezu and Martin, 2013;Martin, 2019;Merlini et al, 2016), provides an elegant solution to the problem of choosing a partner from among two or more similarly-distant candidates. Classical spatial sensing paradigms that integrate spatial information to extract a single "upgradient" direction are poorly suited to this task, as the presence of two or more nearby chemoattractant sources may create a weak or even non-existent net gradient.…”
Section: Advantages Of Exploratory Polarizationsupporting
confidence: 53%
“…Pheromone secretion and sensing factors were enriched at these transient sites, and computational models confirmed that local secretion and sensing/signaling would promote effective partner location in realistic geometries and timescales (Merlini et al, 2016). Thus, an exploratory polarization strategy might be conserved between evolutionarily distant fungi (Martin, 2019).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The advantage of studying mating is that the behavior of wild type cells and cells with mutated polarisomes can be compared within the same mating experiment. Here, neighboring a-and α-cells grow mating projections towards each other until both cells get into a physical contact and fuse to form a diploid cell ( Figure 6A) (Martin, 2019). The polarisomes form at the prospective mating projections of both cells and stay at their tips during growth and cell fusion ( Figure 6A) (Valtz and Herskowitz, 1996;Sheu et al, 2000;Gehrung and Snyder, 1990).…”
Section: Pea2 Recruits Myo2 To the Site Of Cell Fusion During Matingmentioning
confidence: 99%
“…F rom studies on unicellular fungi (yeasts), we understand the mechanism of pheromone signalling in great detail 1,2 . For instance, in Saccharomyces cerevisiae, α-type cells secrete α-pheromone, which is detected by the specific G-protein coupled receptor (GPCR) Ste2 in a-type cells.…”
Section: Sophie G Martinmentioning
confidence: 99%